The peak duration-specific locomotor demands and concurrent collision frequencies of European Super League rugby - Weaving, D.; Sawczuk, T.; Williams, S.; Scott, T.; Till, K.; Beggs, C.; Johnston, R. D.; Jones, B. (Journal of Sports Sciences, 2019)
Understanding the most demanding passages of European Super League competition can optimise training prescription. We established positional and match half differences in peak relative distances (m/min) across durations, and the number of collisions, high-speed- and very-high-speed-distance completed in the peak 10 min period. Moving-averages (10 s, 30 s, 1 min, 5 min, 10 min) of instantaneous speed (m/s) were calculated from 25 professional rugby league players during 25 matches via microtechnology. Maximal m/min was taken for each duration for each half. Concurrently, collisions (n), high-speed- (5 to 7 m/s; m) and very-high-speed-distance (> 7 m/s; m) were coded during each peak 10 min. Mixed-effects models determined differences between positions and halves. Aside from peak 10 s, trivial differences were observed in peak m/min between positions or halves across durations. During peak 10 min periods, adjustables, full- and outside-backs ran more at high-speed and very-high-speed whilst middle- and edge-forwards completed more collisions. Peak m/min is similar between positional groups across a range of durations and are maintained between halves of the match. Practitioners should consider that whilst the overall peak locomotor "intensity" is similar, how they achieve this differs between positions with forwards also exposed to additional collision bouts.